OPTIMALISASI PENGETAHUAN KESEHATAN REPRODUKSI REMAJA PUTRI BERBASIS RESPECTFULL MIDWIFERY CARE (RMC) - Yuria R. A., Mella; Gustina, Irwanti; Chairiyah, Royani (Jurnal Abdi Insani, 2024)
About 33.3% of adolescent girls aged 15-19 years started dating when they were not yet 15 years old. The number of adolescents who have received reproductive health counselling in Indonesia is 25.1%. Limited access to information on reproductive health results in a lack of knowledge, traits and risky behaviours in adolescents that have an impact on the reproductive health status of adolescents. One of the results of the international conference in line with the concept of Respectfull Midwifery Care (RMC) has been agreed on the right to information and reproductive health education. For this reason, the availability of adolescent care health services that can fulfil the health needs of adolescents is needed. This community service is organised to increase awareness and participation of adolescents in maintaining their reproductive health. This community service activity is in the form of reproductive health counselling for class XII students of SMAN 51 East Jakarta, totalling 100 people. This community service was carried out on 7 December 2023 with lecture, discussion, active participation, question and answer, evaluation and follow-up methods. In this activity, students were given pre and postest to measure the level of knowledge about reproductive health. The pretest results showed an average score of 67.3 and the post-test results showed an increase in the average score of 95.7. This activity showed significant results with a pvalue of 0.353 which indicates there is a significant difference before and after counselling. Adolescent girls are subjects who need health education, especially adolescent reproductive health. This service activity is expected to increase students' understanding and awareness and maintain their reproductive health.